PROTECTION OF TEACHER PROFESSION ENCOUNTERED WITH THE RULE OF CRIMINAL LAW ON CHILD PROTECTION - Yanto, Oksidelfa; Iqbal, Muhamad (Tadulako University, 2019)
The purpose of this research is in order to know the legal protection to the profession of teacher who perform disciplinary punishment of learners during the teaching and learning process. In addition, this is also to know the legal protection against learners from acts of violence that occurred in the educational environment. The method applied is a normative legal research method that focuses on legal norms and some research results relevant to the existing problems. The result of research showed in the disciplinary effort for the students there is a pattern of relationship between teachers with learners. The relationship is sometimes confronted with child protection regulations that confront the teacher on existing legal processes, although the teaching profession in carrying out its educational activities is protected by law. The conclusion of this research is the enforcement of discipline by teachers to learners often does not mean anything when encountered with other regulations, namely law of child protection. It certainly raises concerns for educator professions in their efforts to enforce disciplinary rules when encountered with the context of learners who cannot be directed by way of advice.Â